World Economy Winter 2022 - Strong headwinds for global economic activity - Klaus-Jürgen Gern; Stefan Kooths; Nils Sonnenberg; Jan Reents; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW Kiel), 2022)
Global growth has decelerated over the course of the year under the impact of high energy prices and great uncertainty. Monetary policy, which is being tightened very quickly in view of high inflationary pressure across the board, is now also putting a drag on economic activity. Overall, production remained on an upward trend into the fall, with impetus coming from easing supply bottlenecks and the continuing normalization of activity in those sectors of the economy particularly affected by the Covid-19 pandemic. Towards the end of the year, however, economic momentum weakened noticeably further. The major advanced economies in particular are currently facing a period of weak economic activity despite considerable fiscal support measures. At the same time, the problems for the Chinese economy remain significant. While global output (measured on a purchasing power parity basis) at 3.2 percent is expected to grow by 0.3 percentage points more this year than expected in September, we continue to forecast an increase of only 2.2 percent next year. For 2024, our expectation has even been reduced slightly to 3.2 percent, mainly because we do expect the US economy to recover slowly. Inflation is likely to have peaked and is expected to slow significantly over the forecast horizon thanks to lower commodity prices and easing economic tensions. However, underlying inflation is not likely to return to target levels until the end of the forecast period.
Keywords: 330; advanced economies; emerging economies; monetary policy; COVID19; Americas; Asia; Business Cycle World; China; Emerging Markets & Developing Countries; Europe; USA